Experimental evidence rules out mosquitoes as vectors of Lyme disease - Pekľanská, Miriama; Kuníková, Kateřina; Vlčková, Romana; Slabová, Hana; Hartmann, David; Volfová, Karolina; Rudolf, Ivo; Šikutová, Silvie; Rego, Ryan O M; Noriega, Fernando Gabriel; Hajdušek, Ondřej; Perner, Jan; et al. (Parasites & vectors, 2025)
BACKGROUND: Lyme disease, caused by Borrelia burgdorferi sensu lato (s.l.), is the most common vector-borne disease in the Northern Hemisphere, with Ixodes ticks as its primary vectors. However, many patients do not recall tick bites, fueling speculation about alternative transmission routes, particularly via mosquito bites. This belief is reinforced by studies reporting Borrelia presence in mosquitoes. This study evaluates whether three mosquito species can acquire, maintain, and transmit Borrelia spirochetes. METHODS: Mosquitoes (Aedes aegypti, Culex quinquefasciatus, and Culex pipiens biotype molestus) were fed on Borrelia-infected mice to assess pathogen acquisition. Additional experiments involved ex vivo feeding on Borrelia-enriched blood to examine spirochete persistence in the mosquito gut. The potential for mechanical transmission was tested by simulating interrupted feeding between infected and naive hosts. The role of trypsin in Borrelia survival and infectivity was also investigated. RESULTS: Mosquitoes exhibited low efficiency in acquiring Borrelia from infected hosts. Spirochetes artificially introduced through ex vivo blood meals were rapidly eliminated during digestion, primarily due to trypsin activity. Inhibition of trypsin prolonged spirochete persistence and infectivity in the mosquito gut. Mechanical transmission experiments revealed no evidence of Borrelia transmission from infected to naive hosts. CONCLUSIONS: Our findings demonstrate that mosquitoes lack the biological capacity to efficiently acquire and maintain B. burgdorferi s.l. spirochetes and are unable to transmit them through natural or mechanical means. This study provides compelling evidence against mosquito-borne transmission of Lyme disease and reinforces Ixodes ticks as the sole competent vectors, which is crucial for targeted public health interventions and accurate risk communication.
Keywords: Borrelia burgdorferi; Ixodes; Transmission; komáří přenašeči; Lyme disease; Borrelia; Lyme Disease; lymeská nemoc; Female; klíště; zvířata; myši; Culex; Mice; Tick; ženské pohlaví; Mosquito; Mosquito Vectors; Borreliosis; Aedes; Animals